Metal complexes as a possible anticancer therapy: a review of the literature (2021)
Cancer is still one of the groups of multifactorial diseases that causes more deaths worldwide. In fact, emerging resistance to traditional cancer treatments make necessary the analysis of new methods to treat cancer. One of the most successful therapies to handle cancer is the use of metallic complexes, such as cisplatin. Those complexes exhibit unique characteristics, such as variable coordination modes, redox activity and reactivity against an organic substrate. In this way, the design of new metal complexes as antitumor agents has aroused great interest in the scientific community in order to obtain a better anticancer activity, reduce the overcoming secondary effects related to the low selectivity, and obtain affordable and easily accessible treatment for cancer patients.